The Solubility Studies and the Complexation Mechanism Investigations of Biologically Active Spiro[cyclopropane-1,3'-oxindoles] with β-Cyclodextrins - Anna A. Kravtsova; Anna A. Skuredina; Alexander S. Malyshev; Irina M. Le-Deygen; Elena V. Kudryashova; Ekaterina M. Budynina (MDPI AG, 2023)
In this work, we first improved the aqueous solubility of biologically active spiro[cyclopropane-1,3'-oxindoles] (SCOs) via their complexation with different β-cyclodextrins (β-CDs) and proposed a possible mechanism of the complex formation. β-CDs significantly increased the water solubility of SCOs (up to fourfold). Moreover, the nature of the substituents in the β-CDs influenced the solubility of the guest molecule (MβCD > SBEβCD > HPβCD). Complexation preferably occurred via the inclusion of aromatic moieties of SCOs into the hydrophobic cavity of β-CDs by the numerous van der Waals contacts and formed stable supramolecular systems. The phase solubility technique and optical microscopy were used to determine the dissociation constants of the complexes (Kc~102 M−1) and reveal a significant decrease in the size of the formed crystals. FTIR-ATR microscopy, PXRD, and 1H-1H ROESY NMR measurements, as well as molecular modeling studies, were carried out to elucidate the host-guest interaction mechanism of the complexation. Additionally, in vitro experiments were carried out and revealed enhancements in the antibacterial activity of SCOs due to their complexation with β-CDs.